Myrtus Communis Extracts as Biocontrol Agents against Tribolium Castaneum - Khalaf, Thabet Mudheher (Journal of Science in Medicine and Life, 2025)
This study analyzes the effects of Myrtus communis extracts on the behavior of the red flour beetle (Tribolium castaneum), evaluating the impact of aqueous and ethanolic extracts on the attraction and repellency of this insect under laboratory conditions. The results indicate that the effect of M. communis extracts depends on concentration and exposure duration, with mild attraction observed at 1.5% concentration and moderate repellency at 3%, particularly over time. Additionally, the ethanolic extract proved to be more effective than the aqueous extract in achieving repellency. Larvae exhibited no attraction response but showed limited repellency at higher concentrations. From an applied perspective, these findings suggest the potential use of M. communis extract as a natural insect repellent in stored-product pest management strategies, either as a repellent spray or as a component in lure-and-kill traps. However, further studies are needed to identify the active compounds responsible for this effect, explore the enhancement of repellency through blending with other plant oils or using higher concentrations, and assess its efficacy under field conditions to determine its practical applicability in pest control programs.